Modification of optical properties of tungsten exposed to low-energy, high flux deuterium plasma ions - Alimov, V. K.; Belyaeva, A. I.; Galuza, A. A.; Isobe, K.; Konovalov, V. G.; Savchenko, A. A.; Slatin, K. A.; Solodovchenko, S. I.; Voitsenya, V. S.; Yamanishi, T. (National Science Center "Kharkiv Institute of Physics and Technology", 2011)
Anomalous change of optical properties of recrystallized W caused by exposure to D plasma ions at sample temperature of ~535 K was studied by ellipsometry and reflectometry. There is a qualitative difference between the samples reflectivity values measured directly and calculated using ellipsometric data. A physical model of the phenomenon is suggested. It is shown that on the W surface exposed at ~535 К two processes take place 1) blistering and 2) modification of electron structure in the upper-most layer.

Методами еліпсометрії та рефлектометрії виявлено аномальне змінення оптичних властивостей рекристалізованого W внаслідок бомбардування іонами D при температурі ~535 К. Існує принципова різниця між значеннями коефіцієнту відбиття, що отримано рефлектометрією та розраховано за даними еліпсометрії. Запропоновано фізичну модель виявленого ефекту. Показано, що на поверхні W, що опромінено при 535 К, мають місце два процеси: 1) блістерінг и 2) модифікація електронної структури поверхневого шару.
Модифікація оптичних властивостей вольфраму в наслідок опромінення великим потоком низькоенергетичних йонів дейтерієвої плазми
Keywords: recrystallized W; change of optical properties; plasma ions; usion reactors; методи еліпсометрії; методи рефлектометрії; оптичні властивості; рекристалізований W; блістерінг